Prolonged analgesia by adding midazolam and hyperbaric bupivacaine in subarachnoid block for lower uterine caesarian section - Akhtaruzzaman, AK; Banik, D; Akhtar, MF; Roy, J; Haque, MF; Hye, MA (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Oct;19(4):569-75 The abstract of this article is available on the PubMed website